(untitled) (Vietnam Journal of Community Medicine, 2025)
Aim: The incidence of acute kidney injury in neonates is increasing in countries around the world. The aim of this study is to describe the incidence and some causes of acute kidney injury in neonates at the Neonatal Center, National Children’s Hospital. Research subjects: 200 neonatal patients (≤ 30 days old) treated at the Neonatal Center, National Children’s Hospital from January 1, 2022 to June 30, 2022. Method: A Cross-sectional descriptive. Results: The rate of infants with acute kidney injury was 46.5%, the mortality rate was 25.8%, the median age at diagnosis was 5 days old. The most common symptoms were edema (38.7%), hyponatremia (43%), hyperkalemia (12.9%). Some common causes of neonatal acute kidney injury include: neonatal infection (80.6%), antibiotics Aminoglycosides (63%), premature babies (61.3%), and patent ductus arteriosus (60.2%), mother got COVID-19 while pregnant (44.1%). Conclusions: Neonatal acute kidney injury is a disease with complicated etiology, high morbidity and mortality. requiring regular monitoring of renal function for promptly diagnosis and treatment to minimize infant mortality.